Green Human Capital and Firms’ Sustainable Performance: A Moderated Mediation Model of Green Transformational Leadership and Green Competitive Advantage - Islam, Md. Johirul; Hashim, Raemah Abdullah; Wahab, Sazali Abd (SEISENSE (PRIVATE) LIMITED, 2025)
Purpose: This study aims to investigate the impact of green human capital (GHC) on firms’ sustainable performance (SP) with a particular focus on the mediating role of green competitive advantage (GCA) and moderating effect of green transformational leadership (green TFL) in the context of garment firms in Bangladesh.Methodology: Researchers collected data from 271 respondents using the questionnaire survey method. The partial least squares structural equation modeling approach was applied to analyze the data.Findings: The research findings revealed a significant positive correlation between GHC and firms’ SP. It also identified GHC as an essential antecedent of GCA. It was also revealed that GCA has a mediating role in the relationship between GHC and firms’ SP. Finally, while green TFL moderates the direct relationship between GHC and SP, the indirect relationship between GHC and SP through GCA is not moderated by it.Originality: This study contributes to the GHC literature in emerging markets by integrating theoretical perspectives with empirical evidence, offering nuanced insights into how GHC influences SP.Practical Implications: This study provides valuable insights for policymakers and stakeholders, highlighting the importance of developing and utilizing GHC in business operations to enhance SP by implementing green TFL style in the organization and achieving GCA in the market.